The American songbag - Sandburg, Carl, 1878-1967 (New York : Harcourt, Brace & company, 1927)
Melodies and lyrics of American songs, folk-songs, and ballads; many include accompaniment arranged for piano.
Includes bibliographcal references (p. xii-xiii).
Keywords: Songs, English -- United States; Ballads, English -- United States; Folk songs, English -- United States; Folk music